Intermediate accounting : IFRS edition - Kieso, Donald E.; Weygandt, Jerry J. ;Warfield, Terry D. (Singapore : John Wiley & Son, Inc., 2019)
Intermediate Accounting: IFRS Edition provides the tools global accounting students need to understand IFRS and how it is applied in practice. The emphasis on fair value, the proper accounting for financial instruments, and the new developments related to leasing, revenue recognition, and financial statement presentation are examined in light of current practice. Global Accounting Insights highlight the important differences that remain between IFRS and U.S. GAAP, and discuss the ongoing joint convergence efforts to resolve them. Comprehensive, up-to-date, and accurate, Intermediate Accounting: IFRS Edition includes proven pedagogical tools, designed to help students learn more effectively and to answer the changing needs of this course.
1. Financial Reporting and Accounting Standards -- 2. Conceptual Framework for Financial Reporting -- 3. The Accounting Information System -- 4. Income Statement and Related Information -- 5. Statement of Financial Position and Statement of Cash Flows -- 6. Accounting and the Time Value of Money -- 7. Cash and Receivables -- 8. Valuation of Inventories: A Cost-Basis Approach -- 9. Inventories: Additional Valuation Issues -- 10. Acquisition and Disposition of Property, Plant, and Equipment -- 11. Depreciation, Impairments, and Depletion -- 12. Intangible Assets -- 13. Current Liabilities, Provisions, and Contingencies -- 14. Non-Current Liabilities -- 15. Equity -- 16. Dilutive Securities and Earnings per Share -- 17. Investments -- 18. Revenue Recognition -- 19. Accounting for Income Taxes -- 20. Accounting for Pensions and Post-Retirement Benefits -- 21. Accounting for Leases -- 22. Accounting Changes and Error Analysis -- 23. Statement of Cash Flows -- 24. Presentation and Disclosure in Financial Reporting -- A. Specimen Financial Statements: Marks and Spencer Group plc A-1 -- B. Specimen Financial Statements: Adidas AG B-1 -- C. Specimen Financial Statements: Puma SE C-1 --
Includes index.
Keywords: ACCOUNTING